Challenges from left and right: the long-term dynamics of protest and electoral politics in Western Europe. Issue 4 (8th August 2019) - Hutter, Swen; Borbáth, Endre
ABSTRACT: The paper looks at how protest politics has developed in Western Europe since the 1970s and how these developments are related to changes in electoral politics. We take up arguments on the two-fold restructuration of political conflict and its different impact on protest and electoral politics. Most importantly, we highlight that the second wave of political change sweeping across Western Europe since the 1990s with increasing conflicts over immigration and European integration left different marks on protest politics as compared to electoral politics. We argue that this difference reflects the driving forces of change and their preferences for specific political arenas, as the momentum shifted from the libertarian left to the populist radical right. More specifically, the results indicate that challengers from the left and challengers from the right follow different logics when it comes to the interplay of protest and electoral mobilization. Empirically, we rely on two large-scale protest event datasets as well as on data on electoral results and campaigns from the 1970s to 2015.